PENDIDIKAN SEKS DALAM PERSPEKTIF FILSAFAT - Wahyono, Poncojari (Jurnal Bestari, 2008)
Sex abnormality cases in Indonesia increase both in quality and quantity every year which leads to crime. In Indonesia, sex education in formal school is still in argument. Some sure that sex education will decrease sex abnormality if it is given to the studen informal school, but some other doubt it. this argument should be ended with wise decision because is includes the value: what is true and what is not true.sex education not only explains about the sexual organ but also includes the knowledge of changing of biology, psychology and psychosexual as the consequence of human growth. It also related to the knowledge of function of reproduction oragans, moral, ethic and religion. Theaching of sex education in school will involve teacher, student, and material of sex education.Sex education will make students mature. They can distinguish what is true and false. sex education is not identical with sex contact. In order words, sex education will be needed depends on the society itself. It must be considered that students in-their adolescent-are confused and labile. thus, sex education will be needed to quide them.